The oncological and reproductive outcomes of fertility-preserving treatments for stage 1 grade 1 endometrial carcinoma: a systematic review and meta-analysis - M. Olabisi Ogunbiyi; Samuel Oxley; Radha Graham; Adeola Olaitan (Journal of Obstetrics and Gynaecology)
Introduction The number of patients desiring fertility-preserving treatment for endometrial cancer rather than standard surgical management continues to increase.Objective We aimed to evaluate the efficacies of fertility-preserving treatments on the live birth rate, remission and relapse rates for women with stage 1a grade 1 endometrial carcinoma to support patient counselling.Methods We performed a meta-analysis for our primary outcomes of overall remission and relapse rate, and for secondary analysis, we divided papers into treatment type: systemic progestins, intrauterine progestins or hysteroscopic resection and adjuvant hormonal treatment.Results Thirty-five observational studies met inclusion criteria, with a total of 624 patients. Overall, conservative treatment of endometrial cancer showed a remission rate of 77% (95% CI: 70–84%), a relapse rate of 20% (95% CI: 13–27%) and a live birth rate of 20% (95% CI: 15–25%) with more favourable outcomes for the hysteroscopic resection group.Conclusions Hysteroscopic resection and adjuvant hormonal treatment had the most favourable fertility and oncological outcomes. Further high-quality prospective multi-centre trials are warranted to determine the optimal treatment regimen and dosage and risk stratification for these patients.